Removal Process of Cu2+ from Aqueous Solutions using Expanded Vermiculite - Wang, J.H.; Yan, S.Y.; Fan, Y.W.; Chen, Z.Y.; Wang, L. (Asian Journal of Chemistry, 2011)
The adsorption of Cu2+ from aqueous solution by expanded vermiculite was studied in batch mode. The sorption process was fast and equilibrium was achieved in ca. 50 min of contact. The effect of adsorbent dosage, contact time, temperature and initial Cu2+ concentration was investigated. The removal efficiency of Cu2+ using expanded vermiculite reached 99 % in low Cu2+ concentration. Experimental results indicated that a pseudo-second-order reaction model provided the best description of the data with a correlation coefficient 0.99 for different temperatures. The rate constants of adsorption by expanded vermiculite were defined by secondorder kinetics of rate constant 0.0228, 80.878 and 120.280 g/mg/min-1 at 298, 303 and 323 K, respectively. The results indicated that this system was an endothermic process.